1990
DOI: 10.2514/3.10380
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and behavior of laminar gas-jet diffusion flames in microgravity

Abstract: This paper presents the results of studies on the ignition and behavior of cylindrically symmetric, laminar diffusion flames of methane and propane in quiescent air under microgravity conditions. The experiments were conducted in the 2.2 s NASA-Lewis Research Center Drop Tower. The characteristics of gas-jet diffusion flames ignited in microgravity environments have not been reported in the past. In prior research, similar flames were ignited in normal gravity and then subjected to the microgravity condition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 5 publications
6
23
0
Order By: Relevance
“…4 Comparison of predicted soot volume fraction distributions under different gravity level with the peak values indicated flame height in microgravity is obviously taller than that at normal gravity (Kong and Liu 2009). This is in qualitative agreement with the experimental results that the observed microgravity flames are taller than their normal gravity counterparts (Bahadori et al 1990) where the fuel jet is issued into a quiescence environment. The maximum values of soot volume fraction in each case are in the annular region.…”
Section: Resultssupporting
confidence: 81%
“…4 Comparison of predicted soot volume fraction distributions under different gravity level with the peak values indicated flame height in microgravity is obviously taller than that at normal gravity (Kong and Liu 2009). This is in qualitative agreement with the experimental results that the observed microgravity flames are taller than their normal gravity counterparts (Bahadori et al 1990) where the fuel jet is issued into a quiescence environment. The maximum values of soot volume fraction in each case are in the annular region.…”
Section: Resultssupporting
confidence: 81%
“…Typical of many past observations of sootcontaining nonbuoyant laminar jet diffusion flames [8][9][10][11][12][13][14], present flame shapes could be grouped into closed-tip and opened-tip configurations, which were observed for fuel flow rates smaller and larger than the laminar smoke point fuel flow rates, respectively. In fact, the tip-opening phenomenon provided a convenient indicator of laminar smoke points for present test conditions because the associated dramatic change of the shape of the flame tip invariably corresponded to the first observations of soot emissions.…”
Section: Flame Appearancementioning
confidence: 95%
“…In spite of potential effects of unsteadiness for the ground-based studies of nonbuoyant laminanyet diffusion flames, however, Cochran and co-workers [4][5][6], Bahadori and co-workers [7][8][9][10][11][12], and Sunderland et al [14] all observed a linear correlation between luminous flame lengths and fuel flow rates, independent of jet exit diameter, for each fuel burning in air. This behavior also is typical of the luminous flame lengths of buoyant round laminar jet diffusion flames [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations